Advanced HIV disease in the Botswana combination prevention project: prevalence, risk factors, and outcomes. (1st December 2020) - Lebelonyane, Refeletswe; Mills, Lisa A.; Mogorosi, Chipo; Ussery, Faith; Marukutira, Tafireyi; Theu, Joe; Kapanda, Max; Matambo, Stembile; Block, Lisa; Raizes, Elliot; Makhema, Joseph; Lockman, Shahin; et al.
Abstract : Objective(s): To determine the proportion of individuals linking to HIV-care with advanced HIV-disease (CD4 + cell counts ⩽200 cells/μl) in the Botswana Combination Prevention Project, describe the characteristics of these individuals, and examine treatment outcomes. Design: A subanalysis of a cluster-randomized HIV-prevention trial. HIV status was assessed in 16–64-year-olds through home and mobile testing. All HIV-positive persons not on antiretroviral therapy were referred to local Ministry of Health and Wellness clinics for treatment. Methods: Analysis was restricted to the 15 intervention clusters. The proportion of individuals with advanced HIV disease was determined; associations between advanced HIV disease and sex and age explored; and rates of viral suppression determined at 1-year. Mortality and retention in care were compared between CD4 + strata (CD4 + cell counts ⩽200 vs. >200 cells/μl). Results: Overall, 17.2% [430/2499; 95% confidence interval (CI) 15.7–18.8%] of study participants had advanced HIV disease (CD4 + cell counts ⩽200 cells/μl) at time of clinic linkage. Men were significantly more likely to present with CD4 + cell counts 200 cells/μl or less than women [23.7 vs. 13.4%, adjusted odds ratio 1.9, 95% CI 1.5–2.3]. The risk of advanced HIV disease increased with increasing age (adjusted odds ratio 2.2, 95% CI 1.4–3.2 >35 vs. <25 years). Patients with CD4 + cell counts 200 cells/μl or less had significantly higher rates of attrition from care during follow-up (hazards ratio 1.47, 95% CI 1.1–2.1). Conclusion: Advanced HIV disease due to late presentation to or disengagement from antiretroviral therapy care remains common in the Treat All era in Botswana, calling for innovative testing, linkage, and treatment strategies to engage and retain harder-to-reach populations in care. Abstract : Supplemental Digital Content is available in the text